A model of optimising political expenditures to buy government power. Issue 4 (2nd October 2019) - Murphy, Austin
Abstract: This research develops a model of optimal political expenditures and shows how money inevitably controls government leaders, subject only to a single constraint relating to negative public reaction. The paper demonstrates theoretically why many businesses do not make such investments despite abnormally high returns from the expended political capital. In particular, firms with less economic resources optimally recognise that they can successfully participate in the political process only in consortium with the dominant players of mutual interests to influence broader government policies. The largest corporations are therefore able to buy government power with a minimal political outlay.